PENGARUH STRUKTUR ORGANISASI DAN ANALISIS PEKERJAAN TERHADAP EFEKTIVITAS ORGANISASI PADA POLITEKNIK CITRA WIDYA EDUKASI DI BEKASI - Isnainny i (PARAMETER, 2020)
The purpose of this research is to find out the effect of organization structure and job analysis on organization effectiveness. The population included all 68 employees Politeknik Citra Widya Edukasi. The sample consist of 65 persons using saturated sampling. Variabel that being used is organization structure and job analysis as independent variabel, and organization effectiveness as variable dependent. The data were analyzed using multiple linear regression analysis and be processed by SPSS 25.0. Purpose of this research is to see progress of organization effectiveness in Politeknik Citra Widya Edukasi. Primary data are collected to reveal employee perceptions of the effectiveness of organization and their knowledge in organization structure and their job description. Results shows that organization effectiveness for Politeknik Citra Widya Edukasi is less effective because organization structure and job analysis need overview.